Distance, products and travel companions as key drivers to Malaysian tourism demand - Pang, Looi Fai (2017)
To increase tourism’s contribution to the Malaysian economy, the current national policy is to increase tourist arrivals and tourist expenditure. However, tourists are not homogeneous, nor is tourism a single product and studying tourism demand as such will lead to flawed conclusions. Therefore, a disaggregated study of tourists and tourism products would consider the characteristics of different categories of tourists and as such will be more informative and relevant. Hence, the objectives are to firstly study the determinants of tourism demand of Long Haul (LH), Medium Haul (MH) and Short Haul (SH) tourists from the perspectives of tourist arrivals and tourist expenditure, secondly study the demand for the tourism products of accommodation, shopping, food and beverage (F&B) and transportation and thirdly study the demand for accommodation by tourists categorized by travelling companions using the methodology of System Generalised Method Of Moments (SYS GMM), Seemingly Unrelated Regression (SUR), Pooled Ordinary Least Squares (POLS) and Fixed Effect Method (FEM) with Driscoll and Kray standard error correction, whilst applying the Almost Ideal Demand System (AIDS) and Lancaster’s characteristic demand models. The findings indicate that the word of mouth effect is important for all travellers, price of tourism is important for LH travellers, whereas travel cost is an important consideration for MH travellers. Thailand is a complimentary destination for LH, MH and SH travellers, whereas Indonesia is a substitute country for LH and MH travellers and Singapore is a substitute country for MH travellers. The findings from the study of tourism products show that the own price elasticity of shopping and F&B are elastic whereas accommodation and transportation are inelastic indicating that the former goods are luxury goods and the later goods necessities. The cross price elasticity findings indicate that accommodation, shopping and F&B are complimentary goods with prices affecting them in tandem whereas transportation is a substitute good where a change in prices of other tourism goods will affect the demand for transportation in the opposite. The expenditure elasticity indicate that transportation will receive the largest expenditure and shopping the least expenditure when income increases. The findings from the study on the impact of travelling companion on accommodation demand indicate that accommodation is a necessity for all segments of travelling companions. However, the travelling with spouse segment has the least inelastic demand indication that this segment would more likely switch to cheaper accommodation when room rates increase. The familiarity and word of mouth effect is significant, hence word of mouth marketing (WOMM) tactics is essential with monitoring of review webpages and negative reviews swiftly attended to. The varied results obtained when LH, MH, SH were studied indicated that market segmentation and price discrimination policies would be beneficial in achieving the objectives of increase numbers and higher yield. Due to their elastic price elasticity shopping and F&B prices should be kept low whereas accommodation and transportation should be increased. Demand for accommodation varies with the travelling companion, hence price discrimination policies could be applied to different segments.